DIMENSI AGAMA DALAM PEMBANGUNAN NEGARA (KAJIAN TRANSFORMASI PENDIDIKAN ISLAM DI INDONESIA) - Mujiburrahman Mujiburrahman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
Observing the current condition of the Indonesian nation has led to a phenomenon that the country is being hit by the crisis in various aspects of life. Various forms of violation and offense grow and develop in daily life of the community, such as: corruption, collusion, nepotism, and drug (narcotics) and alcohol abuse, theft, robbery and prostitution. In this country, it also begins to emerge the tenet and behavior of radicalism that disturb the community and government. On the other side, nowadays is also faced with the clash and confusion of thought of ‘the contradiction between religion and the State’ embedded to the young generation (millennial generation). The various social problems described above occur due to the low quality of faith and caused the decline of morality and moral degradation of this nation. It needs a fundamental and accurate solution in facing those problems. Improving and rearranging the paradigm, system and orientation of Islamic education according to its framework can be the alternative solution to solve the problems. Islamic education should be a core in the national education curriculum, so that Islamic education will have a complete transformation in people life of this state. A comprehensive and systematic transformation of Islamic education can be done through the following stages: 1) Religious education should be the core in the national education curriculum, and the substance of religious teachings should not be disputed in nation’s life. 2) Religious education in schools and colleges/universities must be taught by qualified and professional teachers and lecturers, and 3) Implementation of religious education materials should fit the needs and age of learners.